Relationship of soil potassium forms with maize potassium contents in soils derived from different parent materials - Butt, Rashid Mehmood; Akhtar, Mohammad Saleem; Mehmood, Ayaz; Imran, Muhammad; Rukh, Shah; Kayani, Ghashiya Sattar; Siddique, Muhammad Tariq; Abbasi, Kashif Sarfraz; Qayyum, Abdul; Ahmad, Zahoor (Italian Journal of Agronomy, 2017)
Understanding of soil potassium (K) dynamics is essential for sustainable crop production. Bioavailability of K depends on forms and distribution within the soil profile. The objectives of this research were to determine which soil K forms control the maize (Zea mays) K contents and compare the extracting capability of sodium tetraphenylborate (NaTPB) with ammonium acetate (NH4OAc) method. Nine soils representing three different parent materials, i.e. loess, sandstone and shale were sampled at three surface genetic horizons. Within each parent material, three soils at varying level of development were selected. Besides basic soil parameters, K was fractioned into water soluble K, exchangeable K, non-exchangeable K, and NaTPB-extracted K. The maize was sown in pots having 2 kg soil from each genetic horizon. Crop was harvested at seven weeks and plant was analysed for K contents. Results show that NaTPB-extracted K gave best correlation as compared to NH4OAc method. This conveys that a non-exchangeable K portion that becomes available to plants can be better estimated by NaTPB method than NH4OAc extraction.